Deformation and Rupture of Thin Steel Plates due to Cumulative Loading from Underwater Shock and Bubble Collapse - Julian J. Lee; Malcolm J. Smith; James Huang; Geoffrey T. Paulgaard (Shock and Vibration)
The damage sustained by rigidly-clamped square steel plates when subjected to close-proximity underwater explosions has been investigated. The test specimens consisted of plates 0.76 mm and 1.21 mm thick made of either ASTM A1008 mild steel or 350 WT structural-grade steel with a low-temperature notch-toughness requirement. The explosively-loaded area of the plates was square, with dimensions of 254 mm X 254 mm. High-explosive charges from 1.1 g to 50 g were used at different standoff distances to obtain different shock strengths and bubble collapse intensities. Although the main impulsive load on the plate was due to the shock impact, because the standoff distances were less than twice the maximum free-field bubble radius, a strong interaction between the detonation product bubble and the target plate caused a rapid water jet to impinge on the plate, resulting in additional loading and damage. As a result, four main regimes of loading and damage were identified: a) holing/petaling due to shock loading, b) edge tearing due to shock loading only, c) edge tearing due to the cumulative loading from shock and bubble collapse, and d) large deformation due to shock and bubble collapse loading. The damage mechanisms and dynamic response of the plates were measured using dynamic displacement sensors, pressure gauges, and high-speed video. A fracture analysis was performed on the damaged plates to analyze the mechanisms of failure. Finally, finite-element analysis using a failure criterion based on normalized shear stress and effective strain has been used to examine the failure limits.